The development of critical thinking competency amongst vocational administrators - Methi Pilanthananond (My University, 1992)
ABSTRACT The development of critical thinking skills amongst educational managers is still in its infancy in Thailand. To assist the development, six learning packages corresponding to the taxonomy of Bloom et al were developed and administered to an experimental group during a course on critical thinking on an MIEd course for educational administration. The results were seen to be significant for those students using the study packages against the control group who just attended the class. Some implication of the findings are discussed.
Keywords: Bloom's taxonomy; Higher Education Learning Practices